Komposit dari sampah plastik fleksibel dan serbuk gergaji - Dwi Wahini Nurhajati; Arum Yuniari; Herminiwati Herminiwati; Sri Brataningsih Puji Lestari (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2003)
A composite made from the flexsible plastic waste and saw dust was studied. The objectives of this research was to find the optimum ratio of the flexible plastic waste and saw dust in its application on a floor tile. The investigated ratio of flexible plastic waste / saw dust were 100/0; 90/10; 80/20; 70/30; 60/40; and 50/50 respectively. The composites were prepared on a rheocord-90 machine at 600C for 10 minutes. The composites were tested for their physical properties I, e flexibility, dimensional stability, curling, volatility, tensile strength, elongation at break, and hardness. The physical properties testing result show that a composite by using the flexible plastic waste and saw dust in comparation of 90/10 could meet the requirements of SNI 03/4060/1996 for Vinyl Floor. The increasing saw dust content in composites decreased tensile strength, elongation at break, flexibility, and hardness, but increased dimensional stability, and volatility. Tensile strength of all composites was higher than particle board. Keywords : composites, flexible plastic waste, saw dust, floor tile.